Antibiotic Resistance of Enterobacteriaceae strains Isolated from Different Animals Gastrointestinal Tracts - Lukáš Hleba; Jana Petrová; Juraj Čuboň; Attila Kántor; Mohammad Ali Shariati; Miroslava Kačániová (Scientific Papers Animal Science and Biotechnologies, 2023)
In this study we monitored antibiotic resistance in Enterobacteriaceae strains isolated from different animals gastrointestinal tracts (GIT). We isolated Enterobacteriaceae from chicken, ducks, lambs, pigs, sheeps, cows and rabbits collected from slovakian farms. Enterobacteriaceae strains were cultivated on MacConkey agar at 35° ± 2°C at 24 hours. Pure cultures of Enterobacteriaceae strains were obtained by four-way streak method on Chromogenic coliform agar. Identification of purified Enterobacteriaceae strains was done by Enterotest 24 and MALDI TOF MS. For susceptibility testing disk diffusion method was used according by EUCAST. We determined the most resistance in Enterobacteriaceae strains against streptomycin, tetracycline, ampicillin, piperecillin, levofloxacine, chloramphenicol and smaller level of resistance against amikacin, ceftriaxone and ofloxacine. Equally we detected resistance to more antibiotics in one strain. The most resistance was Salmonella enterica ser. Typhimurium. Also E. coli was resistance against four antibiotics and Raoultella ornithinolytica too. Antibiotic resistance was found in other isolated strains too.